Predictors of cerebral blood flow during surgery in the Trendelenburg position, and their correlations to postoperative cognitive function - Nordum, Fredrik Hoff; Tveit, Sjur Hansen; Idland, Ane-Victoria; Øyen, Lill Anette; Thomas, Owen Matthew Truscott; Søvik, Signe; Hyldebrandt, Janus Adler (Frontiers in Anesthesiology, 2024)
Background In robot-assisted laparoscopic prostatectomy surgery patients are tilted 30°–40° head-down. Knowledge of cerebral autoregulation and determinants of cerebral blood flow in this setting is limited, though postoperative cognitive impairment has been reported. This observational study describes the hemodynamic determinants of cerebral blood flow and dynamics of cerebral perfusion pressure during surgery in the Trendelenburg position and the correlations with postoperative cognition measures. Materials and methods We included patients scheduled for robot-assisted laparoscopic prostatectomy without known cerebrovascular disease. Cardiac index, mean arterial pressure, central venous pressure, optic nerve sheath diameter as a surrogate for intracranial pressure, ultrasound-measured internal carotid artery (ICA) blood flow and PaCO2 were recorded at six time points (awake, anesthetized, immediately after tilt, 1 h of tilt, just before end of tilt, and before emerging from anaesthesia). Comprehensive cognitive tests were performed before surgery and 10 and 180 days post-surgery. Data was evaluated using linear regression models. Results Forty-four males with a mean age of 67 years were included. Duration of anesthesia was 226 min [IQR 201,266] with 165 min [134,199] in head-down tilt. ICA flow decreased after induction of anesthesia (483 vs. 344 ml/min) and remained lowered before increasing at return to horizontal position (331 vs. 407 ml/min). Cerebral perfusion pressure decreased after 1 h tilt (from 73 to 62 mmHg) and remained lowered (66 mmHg) also after return to horizontal position. Optic nerve sheath diameter increased from mean 5.8 mm to 6.4 mm during the course of surgery. ICA flow correlated positively with cardiac index (β 0.367. 1 L/min/m2 increase corresponding to 92 ml/min increased ICA flow). PaCO2 had a positive effect on ICA flow (β 0.145. 1 kPa increase corresponding to 49 ml/min increased ICA flow), while mean arterial pressure had a negative effect (β −0.203. 10 mmHg increase corresponding to a 29 ml/min decline in ICA flow). We found no evidence of postoperative cognitive dysfunction. Conclusion ICA flow and cerebral perfusion pressure were significantly reduced during robot-assisted laparoscopic prostatectomy surgery. ICA flow positively correlated with cardiac index and PaCO2, but negatively with mean arterial pressure. Postoperative cognitive function was not impaired.